2010
DOI: 10.1038/eye.2010.138
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up with optical coherence tomography and microperimetry in eyes with metamorphopsia after macula-off retinal detachment repair

Abstract: Purpose To report the long-term sequential morphological and functional results in eyes with metamorphopsia after retinal detachment (RD) repair. Patients and methods In six eyes of six patients aged 58.7±11.0 years with metamorphopsia after successful buckling surgery for macula-off RD, best-corrected visual acuity (BCVA), fundus biomicroscopy, Amsler grid test, time-domain optical coherence tomography (TD-OCT) and central 121 microperimetry (MP-1) were performed at months 1, 3, 6, 12, and 18. At 5 to 6 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 23 publications
2
18
1
2
Order By: Relevance
“…These results are consistent with the findings of previous reports [4-8]. In a series of 129 eyes operated on for RD, Okamoto et al [6] reported a 39% incidence of metamorphopsia with a mean M-charts score of 0.3°, which means that metamorphopsia was moderate in intensity.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are consistent with the findings of previous reports [4-8]. In a series of 129 eyes operated on for RD, Okamoto et al [6] reported a 39% incidence of metamorphopsia with a mean M-charts score of 0.3°, which means that metamorphopsia was moderate in intensity.…”
Section: Discussionsupporting
confidence: 83%
“…In a series of 129 eyes operated on for RD, Okamoto et al [6] reported a 39% incidence of metamorphopsia with a mean M-charts score of 0.3°, which means that metamorphopsia was moderate in intensity. Several methods exist to assess metamorphopsia, including the Amsler grid, [4, 5, 7], M-charts [8], differential perimetry, preferential hyperacuity, and shape discrimination hyperacuity tests. Home-monitoring devices based on preferential hyperacuity testing have also recently been proposed to quantify the visual deformations in a more familiar environment [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent OCT findings in patients with metamorphopsia were presence of ERM, disruption of the inner segment/outer segment, cystoid macular edema, macular hole, or subretinal fluid, even though no OCT retinal changes could be detected after rhegmatogenous retinal detachment surgery in 32 out of 50 eyes with metamorphopsia [76]. Rossetti et al [78] also reported that long-standing metamorphopsia could occur after successful macula-off rhegmatogenous retinal detachment repair even without detectable signs of PR disruption on OCT. The persisting metamorphopsia appeared to come from retinal vertical displacement by rhegmatogenous retinal detachment surgery [76].…”
Section: Metamorphopsia In Vitreoretinal Interface Disordersmentioning
confidence: 99%
“…Postoperative visual distortion affects even eyes that regained excellent vision and eyes without detectable photoreceptor disruption in spectral domainYoptical coherence tomography (SD-OCT). 7,8 Consequently, many ophthalmologists consider fovea-on rhegmatogenous RD of recent onset to be a surgical emergency to avoid foveal involvement and minimize photoreceptor damage caused by a foveal detachment. 9Y11 Ho et al 2 reported that urgent surgery should be considered based on the close proximity of the RD border to the fovea, especially if it is within 1 disc diameter, to prevent foveal involvement.…”
mentioning
confidence: 99%